The Sicily Channel surface circulation revisited using a neural clustering analysis of a high‐resolution simulation. Issue 7 (2nd July 2016) - Jouini, Manel; Béranger, Karine; Arsouze, Thomas; Beuvier, Jonathan; Thiria, Sylvie; Crépon, Michel; Taupier‐Letage, Isabelle
Abstract: The Sicily Channel surface circulation is investigated by analyzing the outputs of a high‐resolution ocean model MED12 forced during 46 years by the ARPERA atmospheric fields. Applying a neural network classifier, we show that the surface circulation in the Sicily Channel can be decomposed into 8 modes characterizing the major patterns of that circulation, particularly the Algerian Current separation at the entrance to the Sicily Channel, the features of the Atlantic Tunisian Current and of the Atlantic Ionian Stream. These modes reflect the variability of the circulation in space and time at seasonal and inter‐annual scales. Some modes preferably occur in winter whilst others are characteristic of summer. The mode sequence presents an inter‐annual variability in good agreement with observations. The topography of the Sicily Channel sill plays a major role in steering the circulation. In particular the summer upwelling along the southern coast of Sicily, which is present in several modes, could be explained by a large‐scale density forcing. A combination of barotropic/baroclinic double Kelvin waves generated on both sides of the sill provides a mechanism for explaining the complexity of the surface circulation advecting the surface waters from the Western Mediterranean toward the Eastern Mediterranean, the most salient features of which are the Atlantic Tunisian Current, the Atlantic Ionian Stream and the Tyrrhenian Sicilian Current which is a new feature highlighted by the present study. Key Points: We investigated the seasonal and interannual variability of the Sicily Channel currents We used a neural clustering method We found eight significant modes by processing a 46 year numerical simulation